2017
DOI: 10.4067/s0717-95022017000300018
|View full text |Cite
|
Sign up to set email alerts
|

Body Asymmetries in Young Male Road Cyclists

Abstract: RAUTER, S.; VODICAR, J. & SIMENKO, J.Body asymmetries in young male road cyclists. Int. J. Morphol., 35(3):907-912, 2017. SUMMARY: An anthropometric analysis was conducted on 64 competitive young male road cyclists of different age categories (U17; U19; & U23 years of age). The purpose of the study is to find asymmetries between the left and right side of upper and lower limbs with the NX-16 (TC 2 ) 3D body scanner, which includes measurement of left and right upper arm girth, elbow girth, forearm girth, wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 18 publications
1
15
1
Order By: Relevance
“…The following areas have been investigated: weight categories, the optimal proportion of fat free mass and fat mass (Franchini et al, 2011;Mala et al, 2015b), the dimensions of body segments (Franchini et al), dietary habits, and the effects of fast body weight loss on sport performance (Ljubisavljevic et al, 2015;Mala et al, 2016). Only a few studies have covered morphological symmetry and asymmetry in the bodies of athletes Rauter et al, 2017) and specifically, morphological asymmetry among athletes competing in combat sports Krstulovic et al, 2017;Mala et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The following areas have been investigated: weight categories, the optimal proportion of fat free mass and fat mass (Franchini et al, 2011;Mala et al, 2015b), the dimensions of body segments (Franchini et al), dietary habits, and the effects of fast body weight loss on sport performance (Ljubisavljevic et al, 2015;Mala et al, 2016). Only a few studies have covered morphological symmetry and asymmetry in the bodies of athletes Rauter et al, 2017) and specifically, morphological asymmetry among athletes competing in combat sports Krstulovic et al, 2017;Mala et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This was achieved as evidenced by the pressure gradients between legs showing absolute differences of only 1.4 and 2.7 mmHg for the control and symmetrical garments, respectively, and the corresponding absolute differences in peak pressure at the ankle were also small (0.6 and 0.2 mmHg, respectively). Previous research has found size and symmetry differences between legs, in male cyclists of up to 2% at the calf and knee [21]. As commercially available compression garments are made assuming the geometry of both legs is the same, this may lead to an inconsistent fit on an individuals' legs.…”
Section: Discussionmentioning
confidence: 99%
“…It is common to have size and shape differences between dominant and non-dominant legs. Rauter et al [21] showed knee and calf circumferences to differ between left and right legs in young, male road cyclists. Such leg asymmetry could result in commercially available compression garments eliciting more pressure on one leg than the other, as well as providing an inconsistent fit between participants.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement required no specific skill and took approximately 2 min per participant with “research mode” activated. This InBody 720 was extensively studied with regard to its reliability and validity, and reports showed appropriate to high metric characteristics in various samples, including physically active individuals and athletes [31,32,33].…”
Section: Methodsmentioning
confidence: 99%